Iron-based film material for oil-water separation, preparation method and application thereof
By modifying the iron-based porous foam, an iron-based film material with temperature sensitivity and magnetic responsiveness was prepared, which solved the problems of pollution and cleaning of existing oil-water separation membranes, and achieved efficient and easy-to-clean oil-water separation effect.
Patent Information
- Application Number
- CN202110821677.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-07-20
AI Technical Summary
The existing oil-water separation membranes are prone to contamination during the oil-water separation process and are difficult to clean, resulting in a decrease in separation efficiency and attenuation of membrane flux.
Iron-based porous foam is used as the substrate and modified by silane coupling agent and temperature-sensitive monomer to prepare an iron-based film material with temperature sensitivity and magnetic responsiveness. The material is formed by radical polymerization and has the characteristics of easy cleaning and anti-contamination.
It realizes efficient separation of oil-water separation membrane, with temperature responsiveness and magnetic responsiveness, is easy to clean and operate, has high separation efficiency and low membrane pollution.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of oil-water separation functional materials, and in particular to an iron-based film material for oil-water separation, a preparation method and application thereof. Background Art
[0002] Oily wastewater is a common source of pollution in industrial production and daily life, which seriously endangers the water environment and ecological balance. Membrane separation technology is one of the most effective methods for treating oily wastewater. Commonly used separation membranes are divided into hydrophobic membranes and hydrophilic membranes. In the process of oil-water separation of hydrophobic membranes, oil stains are easily adsorbed and aggregated on the surface, causing membrane flux attenuation and decreased separation efficiency. Hydrophilic membranes can effectively improve anti-pollution ability, but membrane pollution and cleaning problems are still inevitable in long-term operation environments. Therefore, it is extremely necessary to find oil-water separation membranes with excellent performance, surface pollution resistance and easy cleaning. Summary of the invention
[0003] The present invention aims to provide an iron-based film material for oil-water separation, a preparation method and application thereof, so as to provide an oil-water separation membrane whose surface is not easily contaminated and is easy to clean.
[0004] In order to achieve the above-mentioned object, according to one aspect of the present invention, a method for preparing an iron-based thin film material for oil-water separation is provided. The preparation method comprises the following steps: washing the iron-based porous foam and then vacuum drying; dissolving a silane coupling agent with double bonds in an ethanol-water mixed solution and hydrolyzing to obtain a first mixed solution, soaking the iron-based porous foam in the first mixed solution for a certain period of time and then taking it out and drying it to obtain an iron-based porous foam treated with a silane coupling agent; dissolving a temperature-sensitive monomer and an initiator in an organic solvent and stirring them evenly to obtain a second mixed solution; immersing the iron-based porous foam treated with a silane coupling agent in the second mixed solution, and obtaining an iron-based thin film material for oil-water separation through a free radical polymerization reaction.
[0005] Furthermore, the cleaning includes immersing the iron-based porous foam in acetone, ethanol, dilute hydrochloric acid and deionized water in sequence for ultrasonic cleaning.
[0006] Furthermore, the volume ratio of ethanol to water in the ethanol-water mixed solution is 7 to 10:1, preferably 9:1.
[0007] Furthermore, the silane coupling agent with a double bond is one or more selected from the group consisting of vinyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane or vinyltri(2-methoxyethoxy)silane.
[0008] Furthermore, the volume fraction of the silane coupling agent in the first mixed solution is 0.1% to 5.0%.
[0009] Furthermore, the silane coupling agent with double bonds is dissolved in a mixed solution of ethanol and water and hydrolyzed for 1 to 6 hours.
[0010] Furthermore, the iron-based porous foam is immersed in the first mixed solution for 1 to 30 minutes.
[0011] Furthermore, the temperature-sensitive monomer is one or more selected from the group consisting of N-isopropylacrylamide, N,N-dimethylacrylamide or N-ethylacrylamide; the initiator is one or more selected from the group consisting of azobisisoheptanenitrile, azobisisobutyronitrile or dibenzoyl peroxide; and the solvent is one or more selected from the group consisting of toluene, xylene or dimethylethylenediamine.
[0012] Furthermore, the mass fraction of the initiator is 0.1 to 5.0% of the temperature-sensitive monomer; the reaction temperature of the free radical polymerization reaction is 60 to 80° C., and the reaction time is 4 to 10 hours.
[0013] According to another aspect of the present invention, there is provided an iron-based film material for oil-water separation, which is prepared by any of the above-mentioned methods for preparing an iron-based film material for oil-water separation.
[0014] According to another aspect of the present invention, there is provided a use of the above iron-based film material for oil-water separation in the treatment of oily wastewater.
[0015] The oil-water separation iron-based film provided by the present invention has the characteristics of temperature sensitivity, magnetic responsiveness, environmental friendliness, simple preparation, low cost and fast separation speed. DETAILED DESCRIPTION
[0016] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0017] In view of the technical problems mentioned in the background technology, the present invention provides an iron-based film material for oil-water separation that has both temperature sensitivity and magnetism.
[0018] According to a typical embodiment of the present invention, a method for preparing an iron-based thin film material for oil-water separation is provided. The preparation method comprises the following steps: washing the iron-based porous foam and then vacuum drying; dissolving a silane coupling agent with a double bond in an ethanol-water mixed solution and hydrolyzing to obtain a first mixed solution, soaking the iron-based porous foam in the first mixed solution for a certain period of time and then taking it out and drying it to obtain an iron-based porous foam treated with a silane coupling agent; dissolving a temperature-sensitive monomer and an initiator in an organic solvent and stirring them evenly to obtain a second mixed solution; immersing the iron-based porous foam treated with a silane coupling agent in the second mixed solution, and obtaining an iron-based thin film material for oil-water separation through a free radical polymerization reaction.
[0019] The polymer obtained after the polymerization of the thermosensitive monomer is thermosensitive, and a hydrophilic / hydrophobic change will occur near the lower critical solution temperature (LCST). The thermosensitive polymer is hydrophilic below the LCST, which can reduce the adsorption of organic pollutants; the stretching / curling of the thermosensitive polymer molecular chain during the volume phase transition can provide "washing mechanical force" to promote the removal of pollutants. Based on this, the thermosensitive polymer can be used to modify the surface of the iron-based foam to design and prepare an easy-to-clean, anti-pollution oil-water separation membrane. The oil-water separation iron-based film provided by the present invention has the characteristics of temperature sensitivity, magnetic responsiveness, environmental friendliness, simple preparation, low cost and fast separation speed.
[0020] According to a typical embodiment of the present invention, the cleaning includes immersing the iron-based porous foam in acetone, ethanol, dilute hydrochloric acid and deionized water in sequence for ultrasonic cleaning to remove rust, impurities and other substances on the surface.
[0021] Preferably, the volume ratio of ethanol to water in the ethanol-water mixed solution is 7 to 10:1; preferably 9:1.
[0022] According to a typical embodiment of the present invention, the silane coupling agent with double bonds is one or more selected from the group consisting of vinyl trimethoxy silane, γ-methacryloxypropyl trimethoxy silane or vinyl tri (2-methoxyethoxy) silane. The silane coupling agent can be modified to the surface of the iron-based foam, and the double bonds can polymerize with the monomers to modify the polymer to the surface through polymerization. Preferably, the volume fraction of the silane coupling agent in the first mixed solution is 0.1% to 5.0%.
[0023] In a typical embodiment of the present invention, a silane coupling agent with double bonds is dissolved in a mixed solution of ethanol and water and hydrolyzed for 1 to 6 hours. After hydrolysis, the ends of the silane coupling agent are converted into hydroxyl groups, which have a strong interaction with the iron-based material, prompting it to bind to the surface of the iron-based material.
[0024] Preferably, the iron-based porous foam is immersed in the first mixed solution for 1 to 30 minutes to allow the reaction to proceed fully.
[0025] In a typical embodiment of the present invention, the temperature-sensitive monomer is one or more selected from the group consisting of N-isopropylacrylamide, N,N-dimethylacrylamide or N-ethylacrylamide; the initiator is one or more selected from the group consisting of azobisisoheptanenitrile, azobisisobutyronitrile or dibenzoyl peroxide, and the solvent is one or more selected from the group consisting of toluene, xylene or dimethylethylenediamine.
[0026] Poly(N-isopropylacrylamide) (PNIPAM) and its derivatives are temperature-sensitive and undergo hydrophilic / hydrophobic changes near the lower critical solution temperature (LCST). The surface of PNIPAM and its derivatives is hydrophilic below the LCST, which can reduce the adsorption of organic pollutants; the stretching / curling of the molecular chains of PNIPAM and its derivatives during the volume phase transition can provide "washing mechanical force" to promote the removal of pollutants. Based on this, PNIPAM and its derivatives can be used to design and prepare easy-to-clean and anti-pollution oil-water separation membranes.
[0027] Preferably, the mass fraction of the initiator is 0.1 to 5.0% of the temperature-sensitive monomer; the reaction temperature of the free radical polymerization reaction is 60 to 80° C., and the reaction time is 4 to 10 hours.
[0028] In a typical embodiment of the present invention, an iron-based film material for oil-water separation is provided. The iron-based film material for oil-water separation is prepared by any of the above-mentioned methods for preparing an iron-based film material for oil-water separation.
[0029] In a typical embodiment of the present invention, there is provided an application of the iron-based film material for oil-water separation in the treatment of oily wastewater, for example, in the oil-water separation treatment of oilfield produced fluid, crude oil leakage, dock sewage and other systems.
[0030] The beneficial effects of the present invention will be further described below in conjunction with embodiments.
[0031] Example 1
[0032] Preparation of iron-based films with temperature-sensitive and magnetic-responsive properties for oil-water separation
[0033] (1) placing the iron-based porous foam in acetone, ethanol, dilute hydrochloric acid and deionized water in turn under ultrasonication for 10 minutes each, and drying in a vacuum drying oven;
[0034] (2) dissolving 0.3% vinyl trimethoxysilane in a mixed solution of ethanol and water, stirring and hydrolyzing for 5 hours, then immersing the iron-based porous foam cleaned in (1) in the hydrolyzed silane coupling agent mixed solution for 7 minutes, and drying in an oven;
[0035] (3) 3 g of N-isopropylacrylamide and 0.01 g of initiator were dissolved in 20 ml of xylene, and the iron-based porous foam modified with the silane coupling agent in step (2) was immersed in the mixed solution, reacted at 70° C. for 6 hours, and then taken out and dried.
[0036] Example 2
[0037] Preparation of iron-based films with temperature-sensitive and magnetic-responsive properties for oil-water separation
[0038] (1) placing the iron-based porous foam in acetone, ethanol, dilute hydrochloric acid and deionized water in turn under ultrasonication for 10 minutes each, and drying in a vacuum drying oven;
[0039] (2) dissolving 0.1% vinyl trimethoxysilane in a mixed solution of ethanol and water, stirring and hydrolyzing for 3 hours, then immersing the iron-based porous foam cleaned in (1) in the hydrolyzed silane coupling agent mixed solution for 7 minutes, and drying in an oven;
[0040] (3) Dissolve 2 g of N-isopropylacrylamide and 0.04 g of initiator in 20 ml of xylene;
[0041] (4) Immerse the iron-based porous foam modified with the silane coupling agent in step (2) in the above mixed solution, react at 70° C. for 6 hours, and then take out and dry.
[0042] Example 3
[0043] Preparation of iron-based films with temperature-sensitive and magnetic-responsive properties for oil-water separation
[0044] (1) placing the iron-based porous foam in acetone, ethanol, dilute hydrochloric acid and deionized water in turn under ultrasonication for 10 minutes each, and drying in a vacuum drying oven;
[0045] (2) dissolving 0.5% of γ-methacryloxypropyltrimethoxysilane in a mixed solution of ethanol and water, stirring and hydrolyzing for 5 hours, and then immersing the iron-based porous foam cleaned in (1) in the hydrolyzed silane coupling agent mixed solution for 7 minutes, and drying in an oven;
[0046] (3) Dissolve 2 g of N-isopropylacrylamide and 0.06 g of initiator in 20 ml of xylene;
[0047] (4) Immerse the iron-based porous foam modified with the silane coupling agent in step (2) in the above mixed solution, react at 75° C. for 6 hours, and then take out and dry.
[0048] Example 4
[0049] Preparation of iron-based films with temperature-sensitive and magnetic-responsive properties for oil-water separation
[0050] (1) placing the iron-based porous foam in acetone, ethanol, dilute hydrochloric acid and deionized water in turn under ultrasonication for 10 minutes each, and drying in a vacuum drying oven;
[0051] (2) dissolving 0.5% of γ-methacryloxypropyltrimethoxysilane in a mixed solution of ethanol and water, stirring and hydrolyzing for 4 hours, and then immersing the iron-based porous foam cleaned in (1) in the hydrolyzed silane coupling agent mixed solution for 3 minutes, and drying in an oven;
[0052] (3) Dissolve 2 g of N-isopropylacrylamide and 0.06 g of initiator in 20 ml of xylene;
[0053] The iron-based porous foam modified with the silane coupling agent in step (2) was immersed in the above mixed solution, reacted at 70° C. for 6 hours, and then taken out and dried.
[0054] Example 5
[0055] Preparation of iron-based films with temperature-sensitive and magnetic-responsive properties for oil-water separation
[0056] (4) placing the iron-based porous foam in acetone, ethanol, dilute hydrochloric acid and deionized water in turn under ultrasonication for 10 minutes each, and drying in a vacuum drying oven;
[0057] (5) dissolving 5% of γ-methacryloxypropyltrimethoxysilane in a mixed solution of ethanol and water, stirring and hydrolyzing for 4 hours, and then immersing the iron-based porous foam cleaned in (1) in the hydrolyzed silane coupling agent mixed solution for 3 minutes, and drying in an oven;
[0058] (6) Dissolve 2 g of N-isopropylacrylamide and 0.06 g of initiator in 20 ml of xylene;
[0059] The iron-based porous foam modified with the silane coupling agent in step (2) was immersed in the above mixed solution, reacted at 70° C. for 6 hours, and then taken out and dried.
[0060] The performance of the iron-based thin film material products for oil-water separation in Examples 1-5 was tested (the testing method adopts the conventional testing method in the art). The results of the iron-based thin film material products for oil-water separation in Examples 1-5 are similar, and all of them have achieved at least the following technical effects:
[0061] Contact angle test: At a temperature of 10°C, the surface is hydrophilic, the water contact angle in the air is 0°, and the oil contact angle under water is 139.3°, which has the characteristics of super hydrophilicity and underwater oleophobicity. At a temperature of 35°C, the surface is hydrophobic, the water contact angle in the air is 135.2°, and the water contact angle under oil is 152.1°.
[0062] Oil-water separation efficiency test: It can achieve efficient separation of a variety of oil-water mixtures, and the separation efficiency is above 93%.
[0063] Oil-water flux test: The flux to water is up to 15.5×10 4 L m -2 h -1 , the maximum flux for oil can reach 18.1×10 4 L m -2 h -1 .
[0064] Detection method:
[0065] Contact angle test: The contact angle of 5 μL of water or various organic solvents on the prepared samples was measured using the hanging drop method. The water drop or each solvent liquid was tested 5 times and the average value was taken to obtain the corresponding contact angle.
[0066] Oil-water separation efficiency test: Under room temperature, weigh the initial oil component mass, then add it to a beaker with an appropriate amount of distilled water to form an oil-water mixture. Pour the oil-water mixture into a separation tube, and separate the oil and water mixture under the action of gravity. The separation efficiency is the mass ratio of the oil before and after separation.
[0067] Oil-water flux test: The flux of various organic solvents and water is tested under the action of their own gravity. Pour the oil or water to be tested into the above-mentioned oil-water separation device, and measure the volume of organic solvent or water passing through a unit area per unit time.
[0068] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0069] 1) The iron-based film for oil-water separation prepared by the present invention is temperature responsive, being hydrophilic at low temperatures and hydrophobic at high temperatures;
[0070] 2) The iron-based film for oil-water separation prepared by the present invention has magnetic responsiveness and can remotely control the rapid separation of oil-water mixture;
[0071] 3) When the oil-water separation iron-based membrane prepared by the present invention separates oil-water mixture, the water and oil flux is large, the operation is easy, the cleaning is easy, and the membrane pollution is small.
[0072] 4) The oil-water separation iron-based membrane prepared by the present invention can separate light oil-water mixture and heavy oil-water mixture.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an iron-based film material for oil-water separation, characterized in that: The following steps are involved: The iron-based porous foam is cleaned and then vacuum dried; Dissolving a silane coupling agent with a double bond in an ethanol-water mixed solution and hydrolyzing the solution to obtain a first mixed solution, soaking the iron-based porous foam in the first mixed solution for a certain period of time, then taking it out and drying it to obtain the iron-based porous foam treated with the silane coupling agent; Dissolving the temperature-sensitive monomer and the initiator in an organic solvent and stirring the mixture to obtain a second mixed solution; The iron-based porous foam treated with the silane coupling agent is immersed in the second mixed solution to obtain the iron-based thin film material for oil-water separation through free radical polymerization reaction; The temperature-sensitive monomer is one or more selected from the group consisting of N-isopropylacrylamide, N,N-dimethylacrylamide or N-ethylacrylamide; The silane coupling agent with double bonds is one or more selected from the group consisting of vinyl trimethoxy silane, γ-methacryloxypropyl trimethoxy silane or vinyl tris (2-methoxyethoxy) silane; The volume fraction of the silane coupling agent in the first mixed solution is 0.1% to 5.0%; The silane coupling agent with double bonds is dissolved in the ethanol-water mixed solution and hydrolyzed for 1 to 6 hours.
2. The preparation method according to claim 1, characterized in that: The cleaning comprises immersing the iron-based porous foam in acetone, ethanol, dilute hydrochloric acid and deionized water in sequence for ultrasonic cleaning.
3. The preparation method according to claim 1, characterized in that: The volume ratio of ethanol to water in the ethanol-water mixed solution is 7-10:
1.
4. The preparation method according to claim 3, characterized in that: The volume ratio of ethanol to water in the ethanol-water mixed solution is 9:
1.
5. The preparation method according to claim 1, characterized in that: The iron-based porous foam is immersed in the first mixed solution for 1 to 30 minutes.
6. The preparation method according to claim 1, characterized in that: The initiator is one or more selected from the group consisting of azobisisoheptanonitrile, azobisisobutyronitrile or dibenzoyl peroxide, and the solvent is one or more selected from the group consisting of toluene, xylene or dimethylethylenediamine.
7. The preparation method according to claim 1, characterized in that: The mass fraction of the initiator is 0.1-5.0% of the temperature-sensitive monomer; the reaction temperature of the free radical polymerization reaction is 60-80°C, and the reaction time is 4-10 h.
8. An iron-based film material for oil-water separation, characterized in that: The iron-based thin film material for oil-water separation is prepared by the method for preparing an iron-based thin film material for oil-water separation according to any one of claims 1 to 7.
9. Use of the iron-based film material for oil-water separation as claimed in claim 8 in the treatment of oily wastewater.
Citation Information
Patent Citations
Thermo-sensitive polyurethane sponge with controllable hydrophilcity-hydrophobicity conversion, and preparation method and application of thermo-sensitive polyurethane sponge
CN108341989A
Oil-water separation foam and preparation method thereof
CN111318054A